Crystal guava (Psidium guajava L. “Crystal”) treated with gibberelic acid (GA3) : Evaluation of in vitro antioxidant capacities - Fajar Sumi Lestari; Ricson Pemimpin Hutagaol; Srikandi Srikandi (Pascasarjana Universitas Negeri Medan, 2023)
Free radicals can cause many diseases, such as cancer. Antioxidant is a compound that could scavenge free radicals. One of the natural source antioxidants is guava. The application of gibberellic acid (GA3) is known to affect the physicochemical properties and antioxidant content of the fruit. The goals of this research were to investigate the antioxidant activity of skin, flesh and fruit of crystal guava were given additional GA3 treatment with concentration 0; 60; 120; 180; 240; and 300 ppm by determining the value of the Antioxidant Activity Index (AAI) using DPPH; evaluate the total phenolic content (TPC), ferric reducing antioxidant power (FRAP) and physicochemical properties; analyse the correlation between the TPC with AAI DPPH by Pearson’s method. Extraction was performed by the maceration method using acetone 50% mixed with a magnetic stirrer for 1 h. Determination of AAI DPPH, FRAP and the TPC was performed by UV-Visible spectrophotometry. TPC in the flesh and fruit fractions tended to increase and FRAP values in all fractions decreased with GA3 application. The highest TPC and FRAP was given by the G3 treatment on the skin fraction and G0 treatment on the skin fraction. The highest AAI in all fractions was given by the G3 treatment. The TPC was significantly positively correlated with the AAI DPPH of the flesh and fruit fraction extracts (0.250 ≤ r ≤ 0.880), and the skin fraction extracts showed a strong negative correlation between TPC and AAI DPPH (-0.813 < r < -0.973).Keywords: Antioxidant activity; DPPH; FRAP; Gibberellic acid; Psidium guajava